Lung cancer cell‐derived EDA‐containing fibronectin induces an inflammatory response from monocytes and promotes metastatic tumor microenvironment. Issue 5 (4th January 2021) - Amin, Asif; Mokhdomi, Taseem A.; Bukhari, Shoiab; Wani, Zubair; Chikan, Naveed A.; Shah, Basit A.; Koul, Aabid M.; Majeed, Umer; Farooq, Faizah; Qadri, Ayub; Qadri, Raies A.
Abstract: Tumor‐associated macrophages (TAMs) play a pivotal role in facilitating tumor growth and metastasis. This tumor‐promoting propensity of TAMs sets in as a result of their complex cross‐talk with tumor cells mediated primarily by tumor cell‐secreted proteins in the tumor microenvironment. To explore such interactions, we employed an immunoscreening approach involving the immunization of Balb‐c mice with model human lung carcinoma cell line, A549. From serological examination combined with mass spectrometric analysis, EDA‐containing fibronectin (EDAFN ) was identified as a conspicuous immunogenic protein in A549 cell secretome. We showed that A549 secreted EDAFN engages TLR‐4 on THP‐1 monocytes to drive the proinflammatory response via NF‐κB signaling cascade. Conversely, A549 derived EDAFN potentiates their metastatic capacity by inducing epithelial–mesenchymal transition through its autocrine activity. In conclusion, the study proposes a possible mechanism of cellular cross‐talk between lung cancer cells and associated monocytes mediated by lung cancer‐derived EDAFN and resulting in the establishment of proinflammatory and metastatic tumor microenvironment. Abstract : The study proposes lung cancer derived EDAFN as a communicating signal between lung cancer cells and associated monocytes resulting in the establishment of proinflammatory and metastatic tumor microenvironment.